Pola Asuh Orang Tua Dalam Mengatasi Penyimpangan Pada Remaja (Fenomena Klitih Di Yogyakarta) - Widjaja, Adinda Rajabani; Wulandari, Puspita; Komariah, Siti; Supriyono, Supriyono (Jurnal Community, 2024)
Adolescence is a transition period for a person in searching for his or her identity. In searching for their identity, teenagers sometimes commit deviations. Deviations that are currently widespread are acts of klitih. Klitih is a case of deviation in the form of violence and is negative in nature. Seeing the many cases of klitih that occur in society, especially the people of Yogyakarta, it is appropriate for all parties to seek the best solution to suppress and prevent cases of klitih from recurring. One effort that can be made is to increase the role of parental parenting in adolescent development. The research method used is qualitative with descriptive analysis and literature study which presents data based on several relevant opinions from various sources and then analyzes them. This research also aims to find out how parents' parenting patterns deal with deviance in adolescents, with a focus on the klitih phenomenon in Yogyakarta. The results of this research reveal various parenting patterns used by parents in dealing with adolescent deviance, namely klitih. Some parents use an authoritarian approach, while others are more likely to approach a democratic approach. Psychological and social factors also play an important role in parents' decision making regarding the phenomenon of klitih. Thus, parenting styles have a significant influence in overcoming deviations in adolescents, especially in the context of the phenomenon of klitih. This research provides valuable insights for further understanding the relationship between parenting styles and adolescent deviance and provides a basis for more effective prevention efforts.